Boundaries of tropical tropopause layer (TTL): A new perspective based on thermal and stability profiles. Issue 2 (24th January 2017) - Sunilkumar, S. V.; Muhsin, M.; Venkat Ratnam, M.; Parameswaran, K.; Krishna Murthy, B. V.; Emmanuel, Maria
Abstract: The structure of tropical tropopause layer (TTL) is delineated based on static stability criteria. It is defined as the region extending from the level of minimum static stability to the level of maximum static stability. The static stability and dynamic instability steadily increase from the base to the top of the TTL. Radiosonde data from three tropical stations and Constellation Observing System for Meteorology, Ionosphere, and Climate GPS radio occultation (COSMIC) data over the tropics are used for this investigation. This study suggests that in terms of stability, the TTL can further be considered as a composite of three sublayers: a bottom layer (BL), a middle layer (ML), and an upper layer (UL) embedded between the potential temperatures ~350–360 K, ~360–380 K, and 380–420 K, respectively. While the BL is significantly influenced by frequent convective outflows, the influence of convection declines across the ML. Ozone and water vapor mixing ratios show a discernible change in their gradients across these sublayers. Occurrences of small‐scale turbulence and cirrus are maximum in the BL and decrease in the ML and UL. Longitudinally, the BL is broad and the ML and UL are narrow over the deep convective cores. Strength of static stability in the UL (BL) is relatively strong (weak) centered about the equator, with pronounced features over the deep convective regions. These features of static stability centered about the equator in the BL could be attributed to the convective outflows in the troposphere and that in the UL to the dynamic and radiative processes in the upper troposphere and lower stratosphere. Key Points: The TTL boundaries are defined based on static stability criteria In terms of stability, the TTL can be considered to be a composite of three distinct layers Occurrence of turbulence and cirrus maximizes in the bottom layer of TTL and decreases in the middle and upper layers